2023
DOI: 10.3390/ijms24032255
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Stimuli: A Major Challenge during Grain Filling in Cereals

Abstract: Light, temperature, water, and fertilizer are arguably the most important environmental factors regulating crop growth and productivity. Environmental stimuli, including low light, extreme temperatures, and water stresses caused by climate change, affect crop growth and production and pose a growing threat to sustainable agriculture. Furthermore, soil salinity is another major environmental constraint affecting crop growth and threatening global food security. The grain filling stage is the final stage of grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 142 publications
1
8
0
Order By: Relevance
“…This suggested that even moderate reductions in water content affect grain-filling capacity. This observation correlates with the general understanding that grain filling is a highly energy-intensive process, with grain-filling success being highly sensitive to fluctuations in environmental circumstances, including soil-moisture content [39].…”
Section: Barley Height and Head Weight Show Increased Sensitivity To ...supporting
confidence: 81%
“…This suggested that even moderate reductions in water content affect grain-filling capacity. This observation correlates with the general understanding that grain filling is a highly energy-intensive process, with grain-filling success being highly sensitive to fluctuations in environmental circumstances, including soil-moisture content [39].…”
Section: Barley Height and Head Weight Show Increased Sensitivity To ...supporting
confidence: 81%
“…In contrast to the abundant rainfall that was recorded at the experimental site from April to July in 2014, stretching from heading time to maturity, the amount of rain that fell in May and June 2017 was consistently less than the average for the climate ( Figure S3 ), which suggests a sustained moderate drought during anthesis and grain filling. Prolonged water insufficiency early in grain development reduces the number of amyloplasts and endosperm cells, which lowers the capacity of starch accumulation, and ultimately lowers grain weight [ 43 , 44 ]. In 2021, a modest drought during anthesis and a more severe final drought were seen ( Figure S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, a modest drought during anthesis and a more severe final drought were seen ( Figure S3 ). Minor postanthesis water stress can speed up grain filling in wheat by boosting the activity of key catalytic enzymes that convert sucrose to starch, and by remobilizing nonstructural carbohydrates from the vegetative tissues to the grain [ 44 ]. The effects of these patterns of drought (timing and severity) explain well the significantly higher mean TKW value obtained in 2021 than those in 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Grain filling is crucial for growth and extremely responsive to environmental changes ( Teng et al., 2023 ). Wheat showed a trend of decreasing grain weight when the amount of assimilates available was constrained by abiotic factors ( Alvarez Prado et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%